Linkage study of surveillance and hospital admission data to investigate Clostridium difficile infection in hospital patients in Perth, Western Australia. (April 2022) - Collins, Deirdre A.; Marcella, Stephen; Campbell, Michael; Riley, Thomas V.
Abstract: Objectives: Increasing incidence rates of Clostridium difficile infection (CDI) and outbreaks of emerging strains have highlighted the need for continuous monitoring and surveillance of CDI in Australia. Active surveillance captures all hospital-identified CDI cases in Western Australia (WA), where all C. difficile isolates recovered are routinely PCR ribotyped. The aim of this study was to determine incidence rates and descriptive and molecular epidemiology of CDI among patients in Perth, WA using linkage of surveillance and hospital administrative records. Methods: All CDI cases (confirmed by tcdB PCR) from July 2012 to June 2014 captured in the Hospital Infection Surveillance WA dataset for three hospitals were linked with hospital admission records from the Patient Administration System and ribotyping data to calculate incidence rates of CDI and the distribution of various ribotypes (RTs). Results: There were 381 individual cases of CDI identified among 354 hospital patients (including outpatients and ED) who experienced ≥1 CDI episode during the study period. CDI was hospital-associated in 62.7% of cases and community-associated (CA)-CDI in 31.2%. The overall incidence rate was 4.40/10, 000 patient days (PD, 95% CI 3.98–4.86), females across all age groups experienced higher incidence (risk ratio 1.29, p  < 0.05). The risk ratio for CA-CDI was highest (7.76, p  < 0.01) for females vs males aged 15–29 years. Overall, 10.8% of cases were admitted to ICU, 15.2% had a recurrent infection and the mortality rate was 7.2%. C. difficile RT 014/020 predominated (34.9%) among 339 isolates of 71 different RTs. Conclusions: The incidence of CDI in WA is high and RT 014/020 continues to be the dominant molecular type in an otherwise diverse array of strains. High strain diversity suggests CDI cases arise from exposure to many different reservoirs. Highlights: Clostridium difficile infection surveillance data were linked with hospital administrative data for 381 cases of infection. The overall incidence rate of C. difficile infection was 4.4/10, 000 patient days. Incidence was higher in females vs males across all age groups. Females aged 15–29 years had 7.76 × higher risk for community-associated C. difficile infection than males of the same age.